2013
DOI: 10.1093/humrep/det422
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine in human follicular fluid is associated with cellular uptake and metabolism-dependent generation of reactive oxygen species in granulosa cells: implications for physiology and pathology

Abstract: This work was supported by a grant from DFG MA1080/17-3 and in part MA1080/19-1. There are no competing interests.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
32
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 57 publications
4
32
0
Order By: Relevance
“…2). Our results confirmed findings in previous studies, which showed that dopamine induces apoptosis in PCOS-derived GCs (Saller et al 2014). However, our mRNA expression data showed a significant decrease in CASP9, which plays an important role in apoptosis.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…2). Our results confirmed findings in previous studies, which showed that dopamine induces apoptosis in PCOS-derived GCs (Saller et al 2014). However, our mRNA expression data showed a significant decrease in CASP9, which plays an important role in apoptosis.…”
Section: Discussionsupporting
confidence: 92%
“…Women with PCOS present increased MAO activity in hyperluteinized ovaries and GCs, which might be attributed to the increased number of transformed corpus luteum as a consequence of diminished luteolysis (IvaniÅeviÄ-MilovanoviÄ et al 2003, Saller et al 2014). This increased MAO-A/B activity might be associated with the increase in dopamine metabolism in GCs derived from women with PCOS previously described by our group (Gómez et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…A potential role of the sympathetic nerve system in regulating inflammatory processes in PCOS has been proposed (Shorakae et al 2015). Studies in cultured human in vitro fertilization-derived granulosa cells showed that NE and dopamine stimulate the generation of reactive oxygen species (Saller et al 2014). In the present work, it was observed that the SON section decreases nitrite release and the mRNA expression of the inflammatory transcription factor Nfkb in PCO MФ.…”
Section: Figuresupporting
confidence: 53%
“…This is comparable to the situation in the human ovary [3]. The reason and mechanisms for accumulation in the FF remain unknown, but may be related to the expression of NE- and DA-transporters and storage-capacities of GCs with respect to catecholamines [3,4,41] and to the ability of oocytes to metabolize DA to NE [42]. These results establish that a ligand (NE in FF) and its receptor (ADRB-2 in GCs) co-exist in the large antral monkey follicle.…”
Section: Discussionmentioning
confidence: 63%